THE EFFECT OF PROFITABILTY, LIQUIDITY, AND CAPITAL STRUCTURE ON DIVIDEND PAYOUT RATIO (EMPIRICAL STUDY ON INDEX LQ45 COMPANIES LISTED ON INDONESIA STOCK EXCHANGE PERIOD 2014-2018) - Nur Melinda Fatimah (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
This study aims to analyze the effect of Profitability, Liquidity, and Capital Structure on Dividend Payout Ratio in Index LQ45 Companies Listed on the Indonesia Stock Exchange Period 2014-2018. The research method used by researches is descriptive verification by sampling using a purposive sampling technique. The data used in this study in this study are secondary data with the anaysis used is the classic assumption test, multiple linear regression analysis, coefficient test, t-test, and F-test. This study uses SPSS software program version 20. The result of the data after analysis show that partially, Profitability doesn’t have a significant negtive effect on Dividend Payout Ratio, Liquidity and Capital Structure significantly positive effect on Dividend Payout Ratio. While simultaneously Profitability, Liquidity and Capital Structure significantly influence the Dividend Payout Ratio.